Quercus dilatata is now Quercus Himalayana - Bahadur, Kr. N. (Indian Forester, 1971)
The name Quercus dilatata Lindl. ex DC. (1864) is a later homonym of Q. dilatala Rafin. (1838). Rehder (1941) while pointing this out replaced it by Q.florihunda Wall. The last name, however, is illegitimate as it was chosen in contravention of Art. 72 of the Code. Hence, it cannot be adopted as a nomen navum. One of the important Indian oaks, hitherto known as Q. dilatata or Q. floribunda has, therefore, to be renamed. The name Q. himalayana Babadur nom. Nov. is proposed bere as an avowed substitute.